2023
DOI: 10.20535/2521-1943.2023.7.1.277544
|View full text |Cite
|
Sign up to set email alerts
|

Features of the welded seam material crystalliza-tion in Ti-TiB alloy under electron-beam welding conditions

Petro Loboda,
Volodymyr Zvorykin,
Constantine Zvorykin
et al.

Abstract: Natural metal composite materials represent a promising class of modern structural materials that need to be welded. Such materials can be welded by fusion, as has been established with the Ti-TiB alloy as an example. The enhanced operational properties of such materials are determined by the microstructure, which is characterized by the presence of microfibers of borides, carbides, or silicides in the metal matrix. To preserve the mechanical properties of materials in a welded joint, it is necessary to ensure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It was established that during the formation of the weld, the source material undergoes changes that lead to the grinding of boride fibers. Studies into the features of the elemental composition of reinforcing boride fibers [12] have shown that the crystallization of the weld pool occurs under conditions of intense cooling through an incomplete eutectic transformation with the formation of metastable phase formations. Performing thermal annealing [13] allows reducing the thermodynamic imbalance of the structural state and phase composition in the weld.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…It was established that during the formation of the weld, the source material undergoes changes that lead to the grinding of boride fibers. Studies into the features of the elemental composition of reinforcing boride fibers [12] have shown that the crystallization of the weld pool occurs under conditions of intense cooling through an incomplete eutectic transformation with the formation of metastable phase formations. Performing thermal annealing [13] allows reducing the thermodynamic imbalance of the structural state and phase composition in the weld.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…6). In all variants of weld formation, TiB fibers formed a structure of dendritic type branches, the features of which were studied in [12]. It should be noted that no integral orientation of TiB fibers relative to the plane of the welded joint was found.…”
Section: Determination Of Directionality and Distribution Of Fibers O...mentioning
confidence: 99%
See 1 more Smart Citation